Development of Math Journey Game Media Based on Triple Code Model for Dyscalculia Students - Siti Aisyah; Kamid; Khairul Anwar (Jurnal Pendidikan Matematika (JPM), 2026)
In mathematics learning, students often required concrete, interactive, and engaging learning media to help them understand basic arithmetic more easily. Students with dyscalculia required special attention because they experienced difficulties in understanding numbers and basic arithmetic operations. This study aimed to develop an educational game called Math Journey based on the Triple Code Model as an alternative learning medium that supported students with dyscalculia in learning basic arithmetic. The game was designed using verbal activities, visual representations, and magnitude understanding in accordance with the principles of the Triple Code Model through the use of concrete tools in play-based activities. This study employed a Research and Development method using the ADDIE model. The development process involved material experts, learning media experts, and teachers as practitioners to evaluate the feasibility and practicality of the product. The subjects of this study were four elementary school students with dyscalculia. Data were collected through material validation sheets, media validation sheets, teacher practicality assessment sheets, and learning outcome tests. The results showed that the game achieved a material feasibility score of 90.91% and a media feasibility score of 95.68%, both categorized as very feasible. The practicality assessment by teachers reached 100%, indicating a very feasible category. Furthermore, the effectiveness test using the N-gain score yielded a value of 0.78, which indicated that the game media was effective for students with dyscalculia. Overall, the Math Journey game based on the Triple Code Model was proven to be feasible, practical, and effective in supporting basic arithmetic learning and provided an enjoyable learning experience for students with dyscalculia.